FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KONTROL PASIEN HIPERTENSI - Ernawati, Wiwik (Coping: Community of Publishing in Nursing; Vol 2 No 1 (2014): JURNAL EDISI JANUARI-APRIL 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Hypertension is degenerative diseases which become a global health problem. Uncontrolled hypertension leads to its complications. Factors related to hypertension control behavior are knowledge, self role in family, attitude, family support, quality of health care, education from health proffesionals, and access to health services. The purpose this study is to know the related factors to people with hypertension behavior to control their hypertension at community health service. This is an observational analytic study using cross sectional design with 68 respondents. Bivariate analyze shows that knowledge (p= 0,006), self role in family (p=0,000), attitude (p= 0,002), family support ( p= 0,000 ) , quality of health care ( p=0,018 ) , education from health proffesionals (p= 0,009 ) , and access to health services ( p= 0,045 ) are factors related to control behavior of people with hypertension. While multivariate analyze find that self role in family is the most dominant factor related to control behavior of people with hypertension (OR=58,143;CI95%=11,081-305,087). So, health provider should motivate patient to control their blood pressure regularly. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Hypertension, control behavior